Red blood cell distribution width to platelet ratio in neonatal foals with sepsis - Rebeca Scalco; Gabriela Novo deOliveira; Bruna daRosa Curcio; McCaide Wooten; K. Gary Magdesian; Stephanie Takako Hidai; Pranav Pandit; Monica Aleman (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Rapid and accurate markers to aid diagnosis of sepsis are needed in neonatal foals. The CBC variable red blood cell distribution width (RDW) to platelet ratio (RPR) is associated with inflammatory response and linked to poor outcomes of sepsis in human patients. Hypothesis Explore the correlation of RPR with sepsis in neonatal foals and evaluate RPR predictive and prognostic value. Animals Three hundred seventeen hospitalized neonatal foals ≤7 days of age that had a CBC and physical exam performed at admission between 2012 and 2021. Methods Retrospective case‐control study. Clinical records were used to calculate sepsis scores and define groups. Red blood cell distribution width to platelet ratio was calculated and compared between groups (septic vs nonseptic) based on Kruskal‐Wallis and Wilcoxon signed‐rank tests. A multivariate logistic regression model to predict sepsis was created. The cutoff for RPR was obtained based on the maximal Youden Index. The Kaplan‐Meier method and the log‐rank test were used to estimate survival curves and compare survival rates based on RPR. Results Red blood cell distribution width to platelet ratio was significantly higher in septic foals (Median = 0.099, confidence interval [CI] [0.093; 0.108]) than in sick nonseptic (0.085, CI [0.083; 0.089]) and healthy foals (0.081, CI [0.077; 0.086]; P < .0001). Red blood cell distribution width to platelet ratio was able to predict sepsis with high accuracy (AUC = 82.1%). The optimal RPR cutoff for sepsis was 0.09. Conclusions and Clinical Importance Red blood cell distribution width to platelet ratio calculation is practical, inexpensive, and based on CBC‐derived data. Calculation of RPR along with CBC can aid in the diagnosis of sepsis and estimation of outcome.